Meta-analysis identifies four new loci associated with testicular germ cell tumor - Chung, Charles C. (2013)
We conducted a meta-analysis to identify new loci for testicular germ cell tumor (TGCT) susceptibility. In the discovery phase, 931 affected individuals and 1,975 controls from three genome wide association studies (GWAS) were analyzed. Replication was conducted in six independent sample sets totaling 3,211 affected individuals and 7,591 controls. In the combined analysis, TGCT risk was significantly associated with markers at four novel loci: 4q22.2 in HPGDS (per allele odds ratio (OR) 1.19, 95%CI 1.12–1.26, P = 1.11×10(−8)); 7p22.3 in MAD1L1 (OR 1.21, 95%CI 1.14–1.29, P = 5.59×10(−9)); 16q22.3 in RFWD3 (OR 1.26, 95%CI 1.18–1.34, P = 5.15×10(−12)); and 17q22 (rs9905704; OR 1.27, 95%CI 1.18–1.33; P = 4.32×10(−13), and rs7221274; OR 1.20, 95%CI 1.12–1.28 P = 4.04×10(−9)), a locus which includes TEX14, RAD51C and PPM1E. The new TGCT susceptibility loci contain biologically plausible genes encoding proteins important for male germ cell development, chromosomal segregation and DNA damage response.